The school libraries of the Augustinian sisters of the Philippines in Luzon a survey with implications for library service development - Cadelina, Rosario T.; Picache, Ursula G.; Perez, Pilar R.
Suggestions and recommendations are offered to help upgrade the school libraries through the combined effort and assistance of the school administrators, librarians and the congregation as well.
The descriptive survey method of research was used with a questionnaire as the data-gathering tool. Two sets of questionnaires were prepared; one for the librarian of the schools and the other for the faculty members. The librarian's questionnaire aimed to find out whether the library collections, facilities, equipment, services and personnel are adequate to meet the needs of the students and teachers while the faculty's questionnaire tried to find out the extent of library use by the faculty members of the schools. The quantitative standards in the Standards for Media Programs of the American Association of School Librarians, the Manual of Regulations for Private Schools, 1970 edition, and the Proposed Standards for Library Media Centers for the Elementary and Secondary School Libraries were consulted to provide the basic requirements of a functional school library program and serve as a guide in appraising the existing situation of the school libraries.
The result of the survey revealed that majority of the school libraries do not have sufficient books, periodicals and audiovisual materials. This is due to the inadequate budget allotment of the library and as a result of the minimal library fees collected from students. Library quarters are also inadequate to accommodate the growing population of the schools. The study also revealed that there are still schools having combined libraries for grade school and high school students, hence the services the library provides do not meet the needs of the clientele. In terms of collection, there are some libraries with unclassified and uncataloged books due to insufficient staff. In general, majority of the schools need to improve their library services. The library services provided are not so extensive and satisfactory enough to meet the needs of students and teachers. Teachers and librarians do work hand in hand in building the library collections. It was noted, however, that there are school administrators who purchase library books without prior consultation with the librarians thus resulting in unnecessary duplication.
The study was conducted in the seven school libraries run by the Augustinian Sisters in Luzon to find out the present status of the library collections, facilities, equipment, services and personnel.
Thesis (M.L.S.)--University of the Philippines, Diliman
Typescript.
Keywords: Augustinians--School libraries--Philippines--Luzon.; Elementary school libraries--Philippines--Luzon.; Libraries, Catholic--Philippines--Luzon.